Patients' and healthcare professionals' views on a specialist smoking cessation service delivered in a United Kingdom hospital: a qualitative study - Bains, Manpreet; Britton, John; Marsh, John; Jayes, Leah; Murray, Rachael L. (BioMed Central, 2014)
BACKGROUND: Hospital admission provides a powerful opportunity to promote smoking cessation. We explored patients' and healthcare professionals' (HCP) views of a specialist smoking cessation service comprising systematic smoking ascertainment, default provision of pharmacotherapy and behavioural counselling at the bedside, and post-discharge follow-up, in a clinical trial in a United Kingdom teaching hospital.